Birth prevalence of cleft lip and/or palate – a register study of all children born in Sweden years 2000–2020 - Måns Cornefjord; Karin Källén; Kristina Klintö; Mia Stiernman; Anna-Paulina Wiedel; Magnus Becker (Journal of Plastic Surgery and Hand Surgery)
This study investigated the birth prevalence of cleft lip and/or palate (CL/P) in Sweden between 2000 and 2020 using data from the Swedish National Medical Birth Register, which includes over 97% of children born in the country, and its subregister the National Register of Congenital Anomalies. The dataset included 2,230,771 anonymized children, with the variables year of birth, sex and diagnoses according to ICD-10. Computed variables were any CL/P diagnosis, cleft palate without cleft lip (CP), cleft lip with or without cleft palate (CL ± P), bilateral cleft lip with or without cleft palate (BCL ± P), unilateral cleft lip and palate (UCLP), bilateral cleft lip and palate (BCLP), and maternal smoking. Overall cleft birth prevalence was 1.52 / 1,000 births, with a yearly risk ratio of 0.989. Trends in the birth prevalences of different cleft types showed a decrease in CL ± P, BCL ± P, UCLP, and BCLP, while CP birth prevalence remained stable. CL/P, CL ± P, BCL ± P, UCLP, and BCLP were significantly more common in boys than girls, but the opposite was shown for CP. The overall birth prevalence was relatively coherent with previous findings, and the decreasing trend seemed to be attributable to the decreasing occurrence of visible clefts (CL ± P, BCL ± P, UCLP, and BCLP). Possible explanations for this are yet to be examined but could include better management of risk factors, demographic changes, or shifts in attitudes toward cleft pregnancy termination. The study provides reliable epidemiological data on CL/P, suggesting a decreasing birth prevalence and changing distribution of cleft types that may require future adjustments of cleft care protocols.